Multiplex immunophenotyping of human acute myeloid leukemia patients revealed single -cell heterogeneity with special attention on therapy sensitive and therapy resistant subpopulations - Gémes, Nikolett; Rónaszéki, Benedek; Modok, Szabolcs; Borbényi, Zita; Földesi, Imre; Trucza, Éva; Godza, Blanka; László, Zsuzsanna; Csernus, Balázs; Krenács, László; Bagdi, Enikő; Szabó, Enikő; et al. (Frontiers in Immunology, 2025)
IntroductionUnderstanding leukemia-associated immunophenotypes (LAIP) could assist in the design of therapies to ameliorate patient benefits in acute myeloid leukemia (AML). In our study, focusing on single-cell heterogeneity in therapeutic resistance, flow cytometric immunophenotyping of the peripheral blood of therapy-naive and follow-up AML patients versus age and sex-matched healthy controls (HCs) was performed.MethodsThe FACS panel consisted of Viobility 405/520 Fixable Dye, Anti-human CD45, CD19, CD3, CD7, CD33, CD34, CD38, CD64, CD117, CD135, HLA-DR antibodies. Unsupervised clustering algorithms such as Uniform Manifold Approximation and Projection for Dimension Reduction (UMAP) and Flow cytometry data that builds Self-Organizing Maps (FlowSOM) were used to reveal the LAIP. The measurable residual disease (MRD) was monitored by our proposed manual gating. To complement the characterization of peripheral immune cells, Luminex MAGPIX was used to measure the concentration of 31 soluble immune-oncology mediators from the plasma of AML patients and HC.ResultsBoth manual gating, UMAP and FlowSOM showed normalization of LAIP similar to the HC immune landscape following therapy. Eleven metaclusters (MCs) were associated with AML before therapy. The follow-up of AML samples revealed four MCs of therapy sensitive cells, and one MC composed of therapeutic resistant cells (MC12: CD3-CD7-CD33-CD38- CD64- HLA-DR- CD117- CD135-) identified by the FlowSOM analysis. The initial AML blasts in the MRD gate (CD19-, CD45+, CD3-, CD38+/CD34±, CD7+/CD117+, CD117+/CD135+) were detectable at the lowest frequency in our current study at 22 cells per 100,000 (0.022%) CD45+CD3- living singlet parental population. In the plasma of AML patients the levels of BAFF, B7-H2, B7-H4, CD25, MICA, and Siglec-7 were increased versus HCs.ConclusionsThis study focused on understanding the LAIP in AML before and after therapeutic intervention. The study highlights the potential of using single-cell LAIP profiling and immune mediator measurements to monitor therapy response and identify measurable residual disease and therapy resistant cell populations in AML.